Has the Yangtze river economic belt strategy promoted the construction of ecological civilization in the upper reaches of the Yangtze river? - Zhang, Zhiyong; Zhang, Lianjun; Liang, Tian; Cheng, Ling; Fang, Liuhua; Zhao, Bin; Zhang, Jianyu; Wen, Chuanhao (Frontiers in Environmental Science, 2022)
As a regional development strategy based on the world’s third largest river basin unit, the Yangtze River Economic Belt Strategy plays a vital role in building ecological civilization with the core concept of "ecological priority and green development". To study the impact of the Yangtze River Economic Belt strategy on the construction of ecological civilization in the upper reaches of the Yangtze River. This paper uses the entropy power method to measure the level of ecological civilization construction in 37 prefecture-level cities in the upper reaches of the Yangtze River. It examines the impact of the Yangtze River Economic Belt Strategy on the construction of ecological civilization in the upper reaches of the Yangtze River based on the DID method. The study results show that (1) the level of ecological civilization construction in the Yangtze River’s upper reaches has continuously improved from 2003 to 2020. (2) The implementation of the Yangtze River Economic Belt Strategy has a significant positive impact on the construction of ecological civilization in the upper reaches of the Yangtze River. (3) The Yangtze River Economic Belt Strategy can promote the construction of ecological civilization in the upper reaches of the Yangtze River by improving the level of science and technology innovation. (4) The implementation of the Yangtze River Economic Belt Strategy does not significantly impact the level of ecological civilization construction in the regions participating in the Belt and Road Initiative, so it is necessary to pay attention to the synergy between different policies. This study will help to raise the awareness of developing countries on economic development and ecological protection in the river basin, and provide a reference for policymakers.